2008
DOI: 10.1017/s001675680800530x
|View full text |Cite
|
Sign up to set email alerts
|

Late Neoproterozoic amphibolite-facies metamorphism of a pre-Caledonian basement block in southwest Wedel Jarlsberg Land, Spitsbergen: new evidence from U–Th–Pb dating of monazite

Abstract: Southwest Spitsbergen, Wedel Jarlsberg Land, consists of two Proterozoic crustal blocks with differing metamorphic histories. Both blocks experienced Caledonian greenschist-facies metamorphism, but only the southern block records an earlier pervasive M1 amphibolite-facies metamorphism and strong deformational fabric. In situ EMPA total-Pb monazite geochronology from both matrix and porphyroblast inclusion results indicate that the older M1 metamorphism occurred at 643 ± 9 Ma, consistent with published cooling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 39 publications
2
58
0
Order By: Relevance
“…Gavrilenko et al [13] reported a whole rock Rb-Sr age of c. 930 Ma for the Isbjørnhamna Group, based on a three-point isochron, whereas Balashov et al [3] dated zircon separated from the rhyolitic rocks of the Eimfjellet Group, using the traditional U-Pb whole grain technique, and obtained a lower intercept of concordia at 931 ± 54 Ma. These age estimates were discredited by Majka et al [29] and subsequent studies which highlighted methodological problems of the previous studies and presented new geochronological and geological evidence ruling out a possibility of Grenvillian metamorphism record in the Isbjørnhamna Group.…”
Section: Grenvillian Orogenymentioning
confidence: 98%
See 2 more Smart Citations
“…Gavrilenko et al [13] reported a whole rock Rb-Sr age of c. 930 Ma for the Isbjørnhamna Group, based on a three-point isochron, whereas Balashov et al [3] dated zircon separated from the rhyolitic rocks of the Eimfjellet Group, using the traditional U-Pb whole grain technique, and obtained a lower intercept of concordia at 931 ± 54 Ma. These age estimates were discredited by Majka et al [29] and subsequent studies which highlighted methodological problems of the previous studies and presented new geochronological and geological evidence ruling out a possibility of Grenvillian metamorphism record in the Isbjørnhamna Group.…”
Section: Grenvillian Orogenymentioning
confidence: 98%
“…These authors suggested that the obtained ages reflected the latest Neoproterozoic re-heating and speculated that it might have been related to the opening of the early Iapetus Ocean. Majka et al [29] dated metamorphic monazite in the Isbjørnhamna Group and obtained an age of 643 ± 9 Ma (Fig. 2).…”
Section: Torellian Orogenymentioning
confidence: 99%
See 1 more Smart Citation
“…Using previous geochronological data (Manecki et al 1998;Majka et al 2008) and thermometrical results presented in this paper, it is possible to reconstruct the cooling history of the Isbjørnhamna Group. Manecki et al (1998) Majka et al (2008) obtained a 643 My U-Th-total Pb age for monazites located both in the matrix of mica schists and enclosed in garnet porphyro- Neoproterozoic metamorphism in southern Svalbard J.…”
Section: Cooling Ratementioning
confidence: 99%
“…Manecki et al (1998) Majka et al (2008) obtained a 643 My U-Th-total Pb age for monazites located both in the matrix of mica schists and enclosed in garnet porphyro- Neoproterozoic metamorphism in southern Svalbard J. Majka et al blasts, constraining the growth of garnet in the Isbjørnhamna Group at 643 Mya.…”
Section: Cooling Ratementioning
confidence: 99%